2011
DOI: 10.3109/09638288.2011.573058
|View full text |Cite
|
Sign up to set email alerts
|

Becoming connected: the lived experience of yoga participation after stroke

Abstract: The study has generated original findings that suggest that from the perspective of people who have had a stroke yoga participation can provide a number of meaningful physical, psychological and social benefits and support the rationale for incorporating yoga and meditation-based practices into rehabilitation programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 55 publications
5
63
0
Order By: Relevance
“…17 Regarding yoga and stroke recovery, 2 case studies have reported improvements in balance and aspects of QoL, 18,19 whereas qualitative findings from another study support perceived improvement after poststroke yoga in strength, range of motion, and walking. 20 These studies indicate that stroke survivors can physically and cognitively engage in and benefit from yoga. Yoga may be especially effective in improving function poststroke, because it promotes coordination of complex movements, balance, strengthening, and breathing.…”
mentioning
confidence: 99%
“…17 Regarding yoga and stroke recovery, 2 case studies have reported improvements in balance and aspects of QoL, 18,19 whereas qualitative findings from another study support perceived improvement after poststroke yoga in strength, range of motion, and walking. 20 These studies indicate that stroke survivors can physically and cognitively engage in and benefit from yoga. Yoga may be especially effective in improving function poststroke, because it promotes coordination of complex movements, balance, strengthening, and breathing.…”
mentioning
confidence: 99%
“…Results of the qualitative component of this study have been reported elsewhere. 37 Participants were randomly assigned to either a 10-week yoga intervention group or a wait-list control group. Randomization, using concealed allocation procedures, was conducted by a research associate who was external to this study.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…It has been shown to provide benefits comparable to those in non-disabled populations, including better sleep, stress relief and improvements in strength and flexibility, measured through scales including the visual analogue scale (VAS) and the perceived stress scale (PSS) (Curtis et al, 2015;Garrett et al, 2011;McCall et al, 2015;Patel, Newstead & Ferrer, 2012). Although a significant cardiovascular response would not necessarily be expected from adaptive yoga, participants perceive improved cardiovascular fitness (Alexander, Innes, Selfe and Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%